Preliminary Investigation of Essentially Derived Variety of Tea Tree and Development of SNP Markers - Li Li; Xiangru Li; Fei Liu; Jialin Zhao; Yan Zhang; Weiming Zheng; Li Fan (Plants, 2023)
The continuous emergence of Essentially Derived Varieties (EDVs) in the process of tea tree breeding will endanger and affect the innovation ability and development potential of tea tree breeding. In this study, genotyping by sequencing (GBS) technology was used to screen high-quality genomic SNPs for the first time to investigate the derived relationships of 349 tea trees from 12 provinces in China. A total of 973 SNPs uniformly covering 15 tea tree chromosomes with high discrimination capacity were screened as the core SNP set. A genetic similarity analysis showed that 136 pairs of tea trees had a genetic similarity coefficient (GS) > 90%, among which 60 varieties/strains were identified as EDVs, including 22 registered varieties (19 were indisputably EDVs). Furthermore, 21 SNPs with 100% identification of 349 tea trees were selected as rapid identification markers, of which 14 SNP markers could be used for 100% identification of non-EDV. These results provide the basis for the analysis of the genetic background of tea trees in molecular-assisted breeding.